CONCEPT OF FOUR LEVELS OF DEVELOPMENT OF HUMAN ESSENTIAL POWERS AS A METHODOLOGICAL AND THEORETICAL BASIS OF MODERN PHYLOSOPHICAL ANTHROPOLOGY - Сабадуха, В. О. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Analyzed conditions of appearance of dominating phylosophical and anthropological aspect "each human – personality" and proved its exhaustiveness. Proved the necessity of acceptance of concept of "the four development levels of human essential powers" as a new paradigm of human existence.